The Impact of English-Speaking Films and Songs on English Language Acquisition (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the effectiveness of immersion and entertainment in the process of language acquisition, with a specific focus on the utilisation of English films and songs. The statement emphasises the educational value of films, which utilise visual clues and storytelling to facilitate comprehension. It also specifies genres that are particularly helpful for English language learning. An investigation of popular English songs explores the impact of rhythm, repetition, and personal involvement in language acquisition. The cultural observations offered by these media types emphasise the significance of cultural environment in the process of acquiring knowledge. The text explores the challenges associated with relying only on entertainment for language acquisition and emphasises the importance of incorporating traditional learning approaches. The resource provides practical advice for learners and presents case examples of successful language acquisition via films and music, offering a thorough perspective on this language learning strategy.